Opposition Principles and Arguments of Antiglobalization: the World is faced with the Threat of Crisis - Terepishchyi, Sergiusz (Studia Warmińskie, 2014)
After 30 years, the issue of globalization in the modern scientific discourse remains relevant and significant. In this study, the author reflects on the conformity of modern global society to the classical criteria of fairness. Based on the scientific expertise U. Beck and Z. Bauman carried out a detailed analysis of the controversial aspects of modern transnational community.